Dampak Pelatihan Terhadap Kinerja Karyawan: Sebuah Studi Kasus - Ratu Noorita Achmad; Danial Danial; Muh. Rizal Halim; Ulfa Rabiyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study investigates the relationship between employee performance, training, and human resource development at PT. Perkebunan Nusantara XIV in Makassar City. The study reveals findings with major significance for organizational improvement through meticulous data analysis and statistical evaluation. The research conclusively shows a link between employee performance and training. Statistics highlight the crucial influence that training plays in improving employee skills and work effectiveness. These findings support the constancy of this correlation by being in line with earlier studies. It advances our knowledge of organizational behavior and performance dynamics by clarifying the relationship between training and employee performance. The study's findings are insightful for businesses looking to maximize staff productivity through strategic training and human resource development programs. It acts as a manual for businesses hoping to use training to boost productivity and encourage staff development.